2003
DOI: 10.1002/pros.10217
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of prostatic small‐cell neuroendocrine carcinoma

Abstract: Prostate small cell carcinoma expresses a diverse repertoire of genes that reflect characteristics of their NE cell of origin. ASCL1, INA, and SV2B are potential molecular markers for small cell NE tumors and NE cells of the prostate. This small cell NE carcinoma gene expression profile may yield insights into the development, progression, and treatment of subtypes of prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 49 publications
4
40
0
Order By: Relevance
“…To this end, in a previous study, we developed patient prostate tumor-derived xenografts (PDX) of AR-negative SCPC (AR ¡ SCPC) and compared the AR ¡ SCPC gene expression profiles to those of AR-positive adenocarcinomas (AR C ADENO) derived from men with CRPC. 7,8 In line with the findings of others, 9,10 we found that AR ¡ SCPC is characterized by a loss of prostate luminal epithelial markers and a gain of neural progenitor/stem cell markers. Because DNA methylation profiles reflect cellular differentiation, 11 we hypothesized that the DNA methylation profiles of AR ¡ and AR C are distinct and that specific DNA methylation markers might be used to detect AR ¡ disease, which is of therapeutic relevance.…”
Section: Introductionsupporting
confidence: 78%
“…To this end, in a previous study, we developed patient prostate tumor-derived xenografts (PDX) of AR-negative SCPC (AR ¡ SCPC) and compared the AR ¡ SCPC gene expression profiles to those of AR-positive adenocarcinomas (AR C ADENO) derived from men with CRPC. 7,8 In line with the findings of others, 9,10 we found that AR ¡ SCPC is characterized by a loss of prostate luminal epithelial markers and a gain of neural progenitor/stem cell markers. Because DNA methylation profiles reflect cellular differentiation, 11 we hypothesized that the DNA methylation profiles of AR ¡ and AR C are distinct and that specific DNA methylation markers might be used to detect AR ¡ disease, which is of therapeutic relevance.…”
Section: Introductionsupporting
confidence: 78%
“…SV2 is known to participate in the regulation of calcium-mediated synaptic transmission and to play a role in vesicle trafficking by binding to other cell surface proteins [42]. Although SV2 was originally reported to be specifically expressed in the central nervous system, recent studies have shown that it is also distributed in other organs [43,44]. SV2B is reported to be expressed in the microvesicles of pinealocytes, which are rich in process terminals [45].…”
Section: Synaptic Vesicle Protein 2b (Sv2b)mentioning
confidence: 97%
“…9 In biology, they have aggressive properties with increased expression of genes involved in cellular proliferation, the cell cycle, antiapoptosis, and mitosis. 10,11 A recent study used nextgeneration sequencing for molecular characterization of NE tumors of the prostate. 12 The cell cycle kinase AURKA (aurora kinase A) and MYCN are overexpressed and amplified in NE tumors.…”
mentioning
confidence: 99%